The Relationship Between The Use of The HOT Fit Model on e-Puskesmas With The Reliability Dimension - gita arisa; Bambang Budi Raharjo; Dini Afriani; Rifa Rohidah Liyani; Frisca Dewi Yunadi (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
The rapid development of technology is driving the government to improve healthcare services thru digitalization, including e-Puskesmas. The e-Puskesmas application is one of the web-based puskesmas management information systems used to manage patient data from registration, examination, to treatment. However, the problems that arise in the implementation of e-Puskesmas will impact the decline in the quality of services provided by health centers. This study aims to determine the relationship between the use of the Human Organization Technology Net Benefit (HOT Fit) model in e-Puskesmas with the reliability dimension at Cisitu Health Center, Sumedang Regency. The type of research used is quantitative with a descriptive analytic research method and a cross-sectional research design. The sampling technique used is total sampling. The sample in this study consisted of 56 officers using e-Puskesmas. Data was collected using a questionnaire and then analyzed using a chi-square test. The research results show a relationship between human usage of e-Puskesmas with the reliability dimension (p-value 0.001) and no relationship between organizational usage of e-Puskesmas with the reliability dimension (p-value 0.696). It is hoped that the health center will improve its internet network and conduct regular evaluations to monitor the performance of e-Puskesmas at the Cisitu Health Center.